None of Our Wars Ended Where They Began - Tabora, Brylle B. (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
These poems were written shortly after the recent national elections that saw the victory of the late dictator’s son. Like most disaffected voters, bogged down by the upsetting news, I could not bring myself to accept the election results that would herald another Marcos in power and allow for a continuation of the Duterte administration known for its bloody war on drugs. So, these are poems of rage and protest—an anthem railing against a government marked by political dynasties, traditional patronage, deepseated oppression, democratization of disinformation, and human rights abuses. Never again!